Legal Protection In The Industrial Era 4.0 Against Unfair Business Competition Practices In Digital Markets (E-Commerce) In Central Java - Irawan Malebra (International Journal of Educational Research & Social Sciences, 2023)
Digital Market (E-Commerce) is an inevitable market dynamic for businesses and consumers in Indonesia. Unfair business competition in the digital market is new and very different from the conventional market. Law No. 5, the Year 1999, and Law No. 11, the Year 2008, have not translated well regarding unfair business competition behaviour in the digital market because these two regulations have not been able to define the digital market explicitly. This research uses the empirical juridical method with a progressive legal theory approach. Data was collected through an online questionnaire using the SurveyMonkey application for e-commerce-based businesses or digital platforms, with 15 respondents from a community of young entrepreneurs, start-ups, and independent beginners in Semarang. In this study, it is hoped that a formula and consensus on problem-solving for unfair business competition practices in the digital market can be found so that the Central Java Business Competition Supervisory Commission (KPPU), as the competent authority, has a legal solution to provide legal certainty for business actors to compete fairly and reasonably. On the other hand, the hope is to create harmony, justice, and order in society so that the climate for Indonesia's digital economic growth will increase and become the foundation of national development hopes.